Grafite em Vila Velha : a transgressão se faz "presente" - Michalovzkey, Sérgio Ronaldo Skrypnik (2013)
This research is focused on graphite as a possible urban expressions in Vila Velha, metropolitan region of Vitória, state of Espírito Santo. In order to understand it in contemporary times, it was necessary brief historical approach as well as the survey